Deteksi tumbuh kembang anak di TK Prima Bhakti Ciparay Tahun 2020 - Yeni Hendriani (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2020)
Early childhood development has an important role in the development of an individual. In order for a child to have good development, it is necessary to carry out early detection of the child's growth and development with the aim of achieving optimization of a child's development. Data shows an increase in the prevalence of parents who do not regularly monitor their children's growth and development. Monitoring the growth and development of toddlers is carried out in conjunction with early detection of developmental disorders in toddlers so that intervention and simulation can provide optimal results. This community service activity aims to determine children's developmental growth and deviations that occur as well as providing education to parents, especially about the growth and development of pre-school children and the factors that support children's growth and development. The target of the activity is pre-school children and mothers/parents of Prima Bhakti Kindergarten students. The method used in the activity is the KPSP child growth and development detection instrument and to increase parents' knowledge about growth and development, it is carried out through counseling, question and answer discussions and demonstrations on how to stimulate children's growth and development. The results of early detection of growth assessment using the WHO curve showed that 95% had normal stature and normal nutrition and 5% were malnourished. Examination of children's development with the KPSP instrument was 100% developmentally appropriate. The education provided to parents shows that they are active participants in question and answer discussion activities and demonstrations of growth and development stimulation.